(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The study found that farmers' awareness of crop insurance schemes has a positive and insignificant influence on their attitude toward the scheme. However, a lack of awareness hurts farmers' attitudes. Social norms considerably impact behavioural intention, with a C.R. of 1.868. Perceived behaviour control (PBC) has an insignificant influence on behavioural intention, while risk awareness has less impact. Awareness about crop insurance schemes significantly affects farmer behavioural intentions, with a positive attitude (3.45/5.0) and a significant impact on crop insurance behaviour. Perceived behaviour control has less impact on farmer crop insurance behaviour. The analysis considers income, attitude towards crop insurance, behavioural intention, and insurance behaviour as dependent variables. Results show no significant difference in education, attitudes, or insurance behaviour among different groups. Low-income farmers showed significant differences from middle- and high-income farmers, as per Scheffe's post-hoc tests. crop insurance and risk awareness explained a 34% (R squared) variance in farmers' attitude toward crop insurance towards the scheme. Attitude, Perceived behaviour control, social norms, Awareness about crop insurance schemes, and Knowledge about crop insurance, variables explain 43% variance in the behavioural intention of the farmers.